Ianus, Berlin: Forschungsdatenzentrum Archäologie & Altertumswissenschaften - Schäfer, Felix (e-Forschungsberichte des DAI, 2023)
IANUS is a new research centre in Germany for digital data from archaeology and classical studies, funded since 2011 by the DFG and coordinated for the whole community by the DAI. Primary goals will be the long-term preservation, the dissemination, the aggregation and the exchange of digital data to enhance its national and international reuse and interoperability. To achieve these goals different activities have been taken, e.g. the promotion of IT-guidelines, a stakeholder analysis, testbeds, community building and expert talks with established archives.